Rethinking Urban Development in Africa Through Sufficiency: Carbon Budgets, Justice and Planetary Limits - Oluwafemi Adewumi A.; David Ness (SureBuilt Series, 2026)
This paper explores how sufficiency can reframe urban development pathways in Africa, with a focus on Lagos, Nigeria, within the context of climate change, carbon budgets, justice and planetary limits. Drawing on World Sufficiency Lab principles and emerging debates in global climate governance, it argues that dominant narratives of “sustainable development” rarely address the core question of how much is enough, for whom and at what cost. The paper develops a dual understanding of sufficiency that addresses both excess consumption and conditions of deprivation. This is particularly relevant in Nigerian cities where housing shortages, infrastructure deficits and limited access to basic services coexist with patterns of overconsumption and speculative development, including underutilized luxury estates, energy-intensive commercial buildings and prestige infrastructure in cities such as Lagos, Abuja and Port Harcourt, alongside informal settlements and energy poverty. Using carbon budgets as an ethical and policy lens, the paper situates Nigeria’s urbanization within planetary limits while recognizing differentiated responsibilities. It engages climate justice perspectives and argues that urban growth should be guided by use value, social need, and ecological responsibility rather than speculative or extractive logics. Consequently, sufficiency is positioned as a conceptual and epistemological framework for African urban development that enables necessary growth while questioning excess. The paper contributes to closing an educational and knowledge gap in Nigeria, where sufficiency and carbon justice remain underexplored. Degree of Integration of Sustainable Features in Retail Properties in a Sub- Saharan Property Market Matthew Oluwole Oyewole1*, Feranmi Barnabas Oguntolu1, Funmilayo Moyinoluwa Araloyin1 and